Enhanced thermal fatigue resistance of 20Mn2SiCrMo bainitic steel by microstructure stabilization design. (July 2022) - Tian, Yu; Tan, Zhunli; Li, Xianjun; Liu, Yanru; Wang, Rui; lv, Bo; Zhang, Min
Graphical abstract: Highlights: Evaluation of thermal cracks provides a quantitative characterization for bainitic steel thermal fatigue. Thermal fatigue resistance is closely related to microstructure stability. Retained austenite shows stronger thermal fatigue sensitivity because of its transformation to martensite and dynamic carbide precipitation. Abstract: Thermal fatigue properties of 20Mn2SiCrMo bainitic steel used for alternative thermal load environment were analyzed. The results showed that thermal fatigue resistance is closely related to microstructure stability. The higher microstructure stability, the higher thermal fatigue resistance. There are smaller microstructure morphology variations during thermal cycles for the structure of ferrite and carbides in 600 °C tempered condition, demonstrating relatively higher thermal fatigue resistance. While for the mixed structure of ferrite, RA and ε - M 2 C in 300 tempered conditions, the samples show stronger thermal fatigue sensitivity because of stress accumulation by dynamic carbide precipitation and the transformation from retained austenite to martensite. Moreover, a new evaluation rule for thermal fatigue is proposed to quantitatively analyze the damage degree of steel suffering alternative thermal loads effectively.